Peran Intensitas Komunikasi Dan Dukungan Sosial Pasangan Terhadap Kepuasaan Perkawinan Suami/Istri Ditinjau Berdasarkan Jenis Kelamin - Wira Nugraha; Nursari Malueka (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2023)
Abstract This study aims to determine the role between communication intensity and partner's social support on marital satisfaction moderated by gender. In this study, the intensity of communication and social support of partners are part of the independent variables, and gender is a mediator variable. While the dependent variable is marital satisfaction. The subjects in this study were residents in one of the sub-districts in Jogjakarta who were married at the age of 5 to 9 years, had children, and lived in the same house. The number of subjects obtained was 102 people. The data collection method uses the scale of each variable including, the marital satisfaction scale, the communication intensity scale and the partner's social support scale. This study uses the Smart PLS ver. 3.0. The results of this study indicate that communication intensity, partner's social support and gender have a major role in increasing marital satisfaction. It was also found that for men the social support of a partner has more influence on marital satisfaction while for women the intensity of communication has more effect on marital satisfaction. Keywords: Communication;social support; partner; gender